A thermodynamic approach toward defining the limits of biogas production. Issue 12 (25th August 2015) - Muvhiiwa, Ralph Farai; Hildebrandt, Diane; Glasser, David; Matambo, Tonderayi; Sheridan, Craig
Abstract : In this article, the authors present theoretical thermodynamic targets for producing biogas. The research shows the relationship between the mass of substrate used vs the methane produced from a feedstock of glucose and an estimate for that of cellulose. Calculations based on material and energy balances are used to determine the performance target (material and energy limits) of an anaerobic digestion system. These limits cannot be exceeded even if one genetically engineer organisms to increase yield. The results show that all processes that produce methane are feasible from a Gibbs free energy point of view but do not conserve the chemical potential of the feed material. The thermodynamics show that methane production is material and energy limited. The maximum amount of methane that can be formed sustainably is 3 moles per mole of glucose, producing 142 kJ of heat per mole of glucose which needs to be rejected. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4270–4276, 2015